Eruptions and explosions : real tales of violent outbursts - Cummings, Judy Dodge (Mystery & mayhem., 2018)
Presents a series of true stories about disasters caused by eruptions and explosions, such as the volcano of Indonesia or the disaster of Chernobyl.